2011
DOI: 10.1016/j.pmr.2011.08.008
|View full text |Cite
|
Sign up to set email alerts
|

School and the Concussed Youth: Recommendations for Concussion Education and Management

Abstract: Synopsis School learning and performance is arguably the critical centerpiece of child and adolescent development, and there can be significant temporary upset in cognitive processing after a mild traumatic brain injury, also called a concussion. This injury results in a cascade of neurochemical abnormalities, and in the wake of this dysfunction, both physical activity and cognitive activity become sources of additional neurometabolic demand on the brain and may cause symptoms to re-emerge or worsen. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
181
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(188 citation statements)
references
References 42 publications
4
181
1
2
Order By: Relevance
“…The feelings of frustration noted in our study appeared to stem from varied sources, including the nature and longevity of the physical symptoms, interpersonal relationships, and time missed from school and sport. Although these observations validate previous research, 27 the causes of postconcussion emotional dysfunction remain unclear. Physiologic factors, stress and anxiety, not being understood by others, and psychological components may contribute alone or in combination to postconcussion emotional dysfunction.…”
Section: Discussionsupporting
confidence: 87%
“…The feelings of frustration noted in our study appeared to stem from varied sources, including the nature and longevity of the physical symptoms, interpersonal relationships, and time missed from school and sport. Although these observations validate previous research, 27 the causes of postconcussion emotional dysfunction remain unclear. Physiologic factors, stress and anxiety, not being understood by others, and psychological components may contribute alone or in combination to postconcussion emotional dysfunction.…”
Section: Discussionsupporting
confidence: 87%
“…'Smart helmets' are being used in some speciality research centres to standardize the physical force and angular acceleration that accompanies head hits, and the utility of these helmets to measure and predict impacts that may result in concussion is currently under investigation. 36,37 Young people recovering from concussion can experience important challenges, including altered social and academic development, [38][39][40] lower scores on general intelligence tests, and decreased school performance (measured by grade-point average). 39 Lower levels of parental education and child academic achievement both correlate with poorer concussion recovery.…”
Section: Recoverymentioning
confidence: 99%
“…Previous investigators 11,29,30 have found that training efficacy was influenced by training modalities and content. Furthermore, we examined the effect of legislation from only 2 states.…”
Section: Effectiveness Of Concussion Education and Trainingmentioning
confidence: 94%
“…The results presented here suggest several ways in which the design and delivery of concussion education to student-athletes can be improved, building on recommendations from other investigators. 10,29,30 The first recommendation is for state and local officials and educators to work with high schools and their athletic departments to determine why athletes are not reporting receiving education and to work to ensure uniform, effective delivery of concussion education to their athletes, across sports and genders. Nearly 25% of athletes in this study who matriculated to college in the postlegislation era reported not having received concussion education.…”
Section: Effectiveness Of Concussion Education and Trainingmentioning
confidence: 99%